2017
DOI: 10.3892/ijo.2017.4066
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of IGF2BP1 by long non-coding RNA HCG11 suppresses apoptosis of hepatocellular carcinoma cells via MAPK signaling transduction

Abstract: Hepatocellular carcinoma (HCC) is a common malignancy of the liver. HCG11 is a member of long non-coding family, upregulation of which in HCC was proved by our previous study. In the present study, the role of HCG11 in the development of HCC was detected by focusing on the interaction between HCG11 and its target protein insulin-like growth factor 2 mRNA-binding protein 1 (IGF2BP1). The expression status of HCG11 and IGF2BP1 was first investigated with clinical HCC samples. Then the expressions of HCG11 and IG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
72
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(80 citation statements)
references
References 31 publications
4
72
1
Order By: Relevance
“…LncRNA coexpression network was widely used to explore the potential roles of novel lncRNAs in TC. For example, Zhang et al revealed that HCG11 was involved in regulating the MAPK signaling pathway and gene transcription though coexpression analysis [28]. In this study, we constructed a network including 19 downregulated lncRNAs and 2698 mRNAs.…”
Section: Discussionmentioning
confidence: 95%
“…LncRNA coexpression network was widely used to explore the potential roles of novel lncRNAs in TC. For example, Zhang et al revealed that HCG11 was involved in regulating the MAPK signaling pathway and gene transcription though coexpression analysis [28]. In this study, we constructed a network including 19 downregulated lncRNAs and 2698 mRNAs.…”
Section: Discussionmentioning
confidence: 95%
“…IGF2BP1 is a post-transcriptional regulator that affects the stability, translatability, and localization of essential mRNAs involved in tumor cell proliferation, growth, and invasion (reviewed in (50) ). IGF2BP1 is generally assigned oncogenic roles and has been shown to interact with and regulate the expression of genes involved in the MAPK signal transduction pathway (51)(52)(53) , providing a link to the activation of this pathway upon circCDYL KD. The gene PLA2G2A is an extreme outlier upon circCDYL KD with abundance increasing more than 19 times ( P < 3e-218, Wald Test, Figure 5G).…”
Section: Functional Studies Of Circcdyl-rbp Interactions In Hepg2mentioning
confidence: 99%
“…lncRNA HCG11 has been demonstrated to participate in the regulation of cell progression and prognosis in hepatocellular carcinoma and squamous carcinoma (Xu et al, ; Chen et al, ). In addition, downregulation of lncRNA HCG11 in PCa is associated with poor prognosis (Zhang et al, ).…”
Section: Introductionmentioning
confidence: 99%